(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Cerebral palsy has traditionally been thought of as a mobility and gait issue caused by a non-progressive damage to the developing mind. While indicative usual symptoms may occur at an earlier age, the characteristics of this entity develop over time, and the particular cerebral palsy condition may not be recognized until the child is between the ages of 3 and 5. Crouch walk, and severe knee bending when moving, is one of the most prevalent indicators of cerebral palsy. Leg splints, muscle damage, physical therapy, and leg surgeries can all assist children with cerebral palsy enhance their walking skills. Current gait trainers are primarily concerned with managing full joint trajectories, avoiding postural control, and tailoring therapy to a specific patient. Robotic exoskeletons used for adult with total paralysis, this one did not walk for the participant. They used their muscle to walk and assisted robot. The hope is that the device which is use will strengthen a child’s muscle to improve unassisted walking. The use of the CP Walker, a revolutionary mechanical system for children with spastic palsy.